2000
DOI: 10.1128/cdli.7.4.635-640.2000
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Increases Host Resistance to Peritonitis

Abstract: Studies by other laboratories have shown that angiotensin II (AII) can affect the function of cells which comprise the immune system. In the present study, the effect of AII on the function of peritoneal macrophages and peripheral blood monocytes was assessed. In vitro exposure (4 h prior to assay) of peritoneal macrophages from mice and rats to AII increased the percentage of cells that phagocytosed opsonized yeast and the number of yeast per macrophage. Furthermore, AII increased the respiratory burst capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Survival is dependent upon an organism's response to injury: constriction of distal vessels to reduce blood flow, increase in blood pressure to provide continued oxygenation in the presence of an opened circulatory system, acceleration of formed elements into the peripheral circulation from the bone marrow including platelets and erythrocytes to allow clotting and provide oxygen, activation of macrophages to fight infection and increase in lymphocyte numbers to enhance immunity, 48,49 (unpublished observation). Following the acute response to injury, angiogenesis provides revascularization of the damaged sites, ECM formation occurs and neural repair can be accomplished.…”
Section: Discussionmentioning
confidence: 99%
“…Survival is dependent upon an organism's response to injury: constriction of distal vessels to reduce blood flow, increase in blood pressure to provide continued oxygenation in the presence of an opened circulatory system, acceleration of formed elements into the peripheral circulation from the bone marrow including platelets and erythrocytes to allow clotting and provide oxygen, activation of macrophages to fight infection and increase in lymphocyte numbers to enhance immunity, 48,49 (unpublished observation). Following the acute response to injury, angiogenesis provides revascularization of the damaged sites, ECM formation occurs and neural repair can be accomplished.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of AΙΙ against infection are presented in a paper studying bacterial peritonitis in which treatment of rats treated with AII inhibitors resulted in a decreased abscess size and an increase in host resistance [78]. These data were correlated with in vitro experiments showing that AΙΙ treatment increased respiratory burst of rat peritoneal macrophages and increased phagocytosis of rat macrophages and human peripheral blood mononuclear cells.…”
Section: Ace Inhibitors In Other Autoimmune and Infectious Disease Momentioning
confidence: 93%
“…79 Conversely, Ang II improved phagocytosis and inhibited abscess formation during experimental murine peritonitis. 80 In the ATHOS-3 trial, the vast majority of patients had confirmed or suspected sepsis. Ang II infusion at the acute phase of vasodilatory shock of septic origin also may contribute to an unknown degree of inflammation enhancement and bacterial clearance.…”
Section: Angiotensin II In Vasodilatory Shock and Sepsismentioning
confidence: 99%